2013
DOI: 10.1371/journal.pone.0059673
|View full text |Cite
|
Sign up to set email alerts
|

Mitral and Tufted Cells Are Potential Cellular Targets of Nitration in the Olfactory Bulb of Aged Mice

Abstract: Olfactory sensory function declines with age; though, the underlying molecular changes that occur in the olfactory bulb (OB) are relatively unknown. An important cellular signaling molecule involved in the processing, modulation, and formation of olfactory memories is nitric oxide (NO). However, excess NO can result in the production of peroxynitrite to cause oxidative and nitrosative stress. In this study, we assessed whether changes in the expression of 3-nitrotyrosine (3-NT), a neurochemical marker of perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…All animals were maintained at Korea Research Institute of Bioscience and Biotechnology (Ochang, Korea). According to Yang et al (2013), mice aged 2-, 6-, 18-or 30-month old were classified as young, adult, middle-aged, and aged animals, respectively. The mice were housed in temperature (22 ± 2°C)-and humidity (50 ± 5 %)-controlled rooms with a 12-h light/dark cycle for at least 1 week before experimentation.…”
Section: Animalsmentioning
confidence: 99%
“…All animals were maintained at Korea Research Institute of Bioscience and Biotechnology (Ochang, Korea). According to Yang et al (2013), mice aged 2-, 6-, 18-or 30-month old were classified as young, adult, middle-aged, and aged animals, respectively. The mice were housed in temperature (22 ± 2°C)-and humidity (50 ± 5 %)-controlled rooms with a 12-h light/dark cycle for at least 1 week before experimentation.…”
Section: Animalsmentioning
confidence: 99%
“…Murdaugh et al [23] reported that 3-nitrotyrosine (a neurochemical marker of peroxynitrite) and nitrated A2E levels increase in human Bruch's membrane with age. Yang et al [24] examined the age-related changes in 3-nitrotyrosine in the olfactory bulb of mice. They found increased 3-nitrotyrosine expression in mitral and tufted cells in the olfactory bulb of aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors report “middle-age” as early as 8 month old [51], [52], others have considered 10–12 month as the appropriate range [53], [54]. Yet other investigators have gone beyond these age ranges and used 17–18 month mice to refer to “middle-age” [55], [56]. In our study, we used 6–8 month old mice to characterize the inflammatory response associated with the upper age range for the mature adult group, which is typically approximately 6 months [ 57 ] .…”
Section: Discussionmentioning
confidence: 99%